2000
DOI: 10.1002/(sici)1097-4636(200004)50:1<59::aid-jbm9>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Particulate retrieval of hydrolytically degraded poly(lactide-co-glycolide) polymers

Abstract: This article describes a technique for the retrieval of polymeric particulate debris following advanced hydrolytic in vitro degradation of a biodegradable polymer and presents the results of the subsequent particle analysis. Granular 80/20 poly(L-lactide-co-glycolide) (PLG) was degraded in distilled, deionized water in Pyrextrade mark test tubes at 80 degrees C for 6 weeks. Subsequently, a density gradient was created by layering isopropanol over the water, followed by a 48-h incubation. Two opaque layers form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This difference may be explained by the precise method used in this study of collecting all residual material with a size larger than 0.45 um. This is in accordance with the research of Cordewener et al22 They also used a precise method to collect remaining particles of biodegradable polymers and they found remnants that were thought to degrade completely. The ISO standard on testing the in vitro degradation of implants17 does not mention any pore size of the filter used for the collection of the remaining material, and therefore we have chosen to use the 0.45 μm filter mentioned in literature 22…”
Section: Discussionsupporting
confidence: 90%
“…This difference may be explained by the precise method used in this study of collecting all residual material with a size larger than 0.45 um. This is in accordance with the research of Cordewener et al22 They also used a precise method to collect remaining particles of biodegradable polymers and they found remnants that were thought to degrade completely. The ISO standard on testing the in vitro degradation of implants17 does not mention any pore size of the filter used for the collection of the remaining material, and therefore we have chosen to use the 0.45 μm filter mentioned in literature 22…”
Section: Discussionsupporting
confidence: 90%
“…The scans showed an ester carbonyl stretch from the PLGA (C@O) at 1747 cm À1 in all the scaffolds with no significant shift due to nano-HA interaction. Other major peaks observed were the CAOAC ether group at 1083 cm À1 , CAO stretch at 1128 cm À1 , A-type CAOAC symmetric stretching at 1181 cm À1 , OAH deformation at 1264 cm À1 , methyl group CAH stretching at 1452 cm À1 and other methylene, methyl groups at 2800-3300 cm À1 [30]. For the nanocomposite scaffolds, a PO 4 3À stretching (1030 cm À1 ) and bending (570 cm À1 ), typical of HA, were observed with intensities varying proportionally with the nano-HA concentration.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…This copolymer can sustain the rigidity for 2 months (adequate time for the fracture repair) and has an overall resorption time of 9-12 months, mainly through hydrolysis. Clinical and experimental studies have demonstrated the safety and efficiency of using the Lacto Sorb 1 system for craniomaxillofacial applications [6][7][8][9][10][11]13,18,20,[21][22][23] .…”
mentioning
confidence: 97%